GAYA BAHASA MAMAH DEDEH PADA CERAMAH BERJUDUL “ISLAM DAN GAYA HIDUP” - Setiawan, Eko Agoes (STID Al-Hadid, 2021)
This research describes figurative language used by Mamah Dedeh, an Islamic preacher, in her sermon titled “Islam dan Gaya Hidup” under the approach of Gorys Keraf’s figurative language theory. A preacher needs to pay attention on his/her figurative language when s/he conveys da’wah messages. Figurative language is considered as the one which can amplify a meaning to someone’s subconscious. Types of figurative language used should be able to make messages which strongly attach to the mind of congregation. This study uses qualitative approach applying analysis technique of figurative language. Its data was collected from the sermon transcript in YouTube. It indicates that personification and repetition were applied during her introduction to build a common understanding, simile was used during the content to simplify realities, paradox was for amplifying the meaning, and erotesis-elipsis-inuendo was applied to emphasize and deepen on the world and hereafter’s lives. At the end of her sermon, she used personification to remind her messages. The usage of figurative language used by Mamah Dedeh was so related to her theme of the lifestyle in Islam such as the way a woman dresses, the way a woman accessorizes, and lives in luxury.